Nail changes in various dermatoses: an observational study conducted at tertiary care center, Ujjain, Madhya Pradesh, India - Kumar, Ujjwal; Varma, Krishnendra; Shayalwar, Ankur (International Journal of Research in Dermatology, 2020)
Background: Nail apparatus forms an integral part to be examined for all dermatological conditions. Nail changes are seen in various dermatosis like psoriasis, onychomycosis, lichen planus, collagen vascular disease, vesicobullous diseases and other papulosquamous diseases. Aims and objective of the study was to determine the prevalence of nail changes in various dermatological conditions. Methods: After applying inclusion and exclusion criteria, 269 cases with various nail changes were enrolled in the study. Detailed history and thorough nail examination was carried out along with other necessary investigations like CBC, RFT, LFT, nail clipping for fungal hyphae culture and microscopy. Results: Out of 269 cases with nail disorders, male to female ratio was 1.5:1 and most common age group was 31-40 years. The most common abnormality observed was onychomycosis (34.2%) followed by nail changes in psoriasis (30.4%), LP (18.5%), eczema (4%), trachonychia (3.3%), paronychia (2.9%), lichen striatus (2.2%) and darier’s disease (0.37%). Among onychomycosis most common pattern observed was DLSO (82.6%) followed by PSO (7.6%), SWO (5.4%) and TDO (4.34%). The pattern of nail changes in psoriasis patients was pitting (30.4%), subungual hyperkeratosis (21.9%) and onycholysis (10.9%). Cases with LP had longitudinal striations (52%), thinning of nail plate and trachonychia (10% each). V shaped notching and distal splitting was seen in one of the Dariers’ disease patient. Conclusions: Nail changes form an indispensible part of various dermatological conditions. The pattern of involvement is unique in each and every disease. Hence examination of all the 20 nails should never be missed.